Co-Crystal of Rosiglitazone With Berberine Ameliorates Hyperglycemia and Insulin Resistance Through the PI3K/AKT/TXNIP Pathway In Vivo and In Vitro - He, Qichen; Chen, Bo; Wang, Gang; Zhou, Duanfang; Zeng, Hongfang; Li, Xiaoli; Song, Yi; Yu, Xiaoping; Liang, Wenxin; Chen, Huiling; Liu, Xu; Wu, Qiuya; et al. (Frontiers in Pharmacology, 2022)
Background: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disease characterized by insulin resistance and hyperglycemia. This study examined the effect and elucidated the mechanism of improvement of hyperglycemia and insulin resistance by a co-crystal of rosiglitazone with berberine (RB) in high-sugar high-fat diet(HSHFD)-induced diabetic KKAy mice. Methods: Diabetic KKAy mice were randomly divided into seven groups: KKAy model control group (DM control) treated with 3% sodium carboxymethyl cellulose; RB groups, administered daily with RB 0.7 mg/kg (RB-L), 2.11 mg/kg (RB-M), or 6.33 mg/kg (RB-H); positive control groups, administered daily with rosiglitazone 1.04 mg/kg (RSG), berberine 195 mg/kg (BBR), or combination of 1.04 mg/kg RSG and 1.08 mg/kg BBR (MIX). Test compounds were administered orally for eight weeks. Non-diabetic C57BL/6J mice were used as normal control (NC). Blood glucose, food intake, body weight, glucose-lipid metabolism, and pathological changes in the pancreas and liver were examined. We further evaluated the mechanism of action of RB in C2C12 and HepG2 cells stimulated with high glucose and palmitate. Results: RB treatment improved glucolipid metabolism and insulin resistance in diabetic KKAy mice. RB reduced blood glucose levels, white fat index, plasma triglycerides (TG), low-density lipoprotein (LDL), gastric inhibitory peptides (GIP), and insulin levels, increased the levels of plasma glucagon-like peptide-1(GLP-1), high-density lipoprotein (HDL), and glycogen content in the liver and muscle; and improved oral glucose tolerance test (OGTT), insulin tolerance test (ITT), and pathological changes in the pancreas and liver of KKAy mice. Moreover, RB upregulated p-PI3K and p-AKT levels and reduced TXNIP expression in KKAy mice and in HepG2 and C2C12 cells. Conclusions: These data indicate that RB ameliorates insulin resistance and metabolic disorders, and the mechanism might be through regulating the PI3K/AKT/TXNIP signaling pathway. Thus, the co-crystal drug RB may be considered as a potential antidiabetic agent for future clinical therapy.